Baseline characteristics of patients with transthyretin amyloid cardiomyopathy enrolled in a tafamidis expanded access programme. (14th October 2021) - Rozenbaum, M H; Ionescu, I; Clausen, M; Lopez, M; Sultan, M B; Attal, S
Abstract: Background: Transthyretin amyloid cardiomyopathy (ATTR-CM) is a progressive and ultimately fatal disease caused by the accumulation of amyloid fibrils in the heart muscle. Tafamidis, currently the only approved drug for the treatment of ATTR-CM, demonstrated reduced mortality and cardiovascular-related hospitalisations in the Tafamidis in Transthyretin Cardiomyopathy Clinical Trial (ATTR-ACT). Real-world data in patients with ATTR-CM, including patient characteristics, are scarce. Here we analysed the baseline characteristics of patients enrolled in an expanded access programme (EAP) for tafamidis. Initiated in 2018, this tafamidis EAP allows access to tafamidis for patients who have exhausted all standard-of-care options and are not eligible for a clinical trial. Purpose: To examine baseline characteristics of patients with ATTR-CM enrolled in a tafamidis EAP. Methods: All patients enrolled in this tafamidis EAP from the start (May 2018) until November 2020 were included. To be eligible for inclusion, patients had to have documentation of the following: genetic testing for transthyretin amyloidosis (TTR sequencing); ATTR-CM diagnosis, including the criteria used; exclusion of light chain amyloidosis; and current medical/cardiac status, including New York Heart Association (NYHA) functional classification. Patients were grouped for analysis purposes in the following NYHA classes: I–II, >II–III, and >III–IV. Results: A total of 700 patients (88.7% male) from 20 countries were enrolled over 2.6 years. Mean age was 76.2 years in males and 76.6 years in females. Of 518 patients with a recorded genotype, 87.5% were wild-type (89.6% male) and 12.5% hereditary (73.8% male). In males and females, respectively, mean age was 77.0 and 79.4 years in wild-type patients, and 66.2 and 69.3 years in variant patients. The NYHA class distribution is shown in the Figure. The greatest proportion of patients was considered NYHA class I–II. The proportion of patients considered NYHA class I–II was lower in the first half of the data collection period (Months 0–15, 55.3%) compared with the latter half (Months 15–30, 59.4%). In 254 patients with baseline N-terminal pro-B-type natriuretic peptide (NT-proBNP) data, the median NT-proBNP level was 2784.5 pg/mL (NYHA class I–II, 2408.5 pg/mL; NYHA class >II–III, 3165.0 pg/mL). Conclusions: These are the first multi-country, real-world data evaluating baseline characteristics of patients with ATTR-CM enrolled in an EAP. It is of interest that, compared with the ATTR-ACT population, this patient group was older and had a greater proportion of wild-type patients. As a higher percentage of patients with less severe disease was enrolled in the latter half of data collection, these data also suggest a potential shift over time to earlier diagnosis of ATTR-CM. This analysis provides insight into the characteristics of real-world patients with ATTR-CM. FUNDunding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Pfizer